2014
DOI: 10.1177/1534734614534442
|View full text |Cite
|
Sign up to set email alerts
|

Sulodexide as Adjunctive Therapy in Diabetic Foot Patients With Critical Limb Ischemia Treated With Percutaneous Transluminal Angioplasty

Abstract: We evaluated the safety and efficacy of sulodexide, a biocompound of glycosamin-glicans, as adjunct medical therapy to percutaneous transluminal angioplasty (PTA) in diabetes mellitus (DM) patients with critical limb ischemia (CLI). We studied 27 consecutive DM patients with CLI successfully subjected to PTA who, on top of standard antiplatelet therapy, received sulodexide 25 mg bid, and were followed-up for 24 weeks, monitoring adverse events, transcutaneous oxygen tension (TcPO), ankle-brachial pressure inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
(29 reference statements)
0
6
0
1
Order By: Relevance
“…Batroxobin (5 IU/0.5 ml), 2 doses before and 4 doses post-procedure1241/267 (lesion)15.4n.s.Aspirin + batroxobin28/244 (lesion)11.4 Major amputation (above ankle amputation) Wang et al [34]RCTIntraluminal and/or subintimal angioplastyFemoro-popliteal and infra-poplitealAspirinAspirin (100 mg/day) from admission day to at least 12 months if no side effects. Batroxobin (5 IU/0.5 ml), 2 doses before and 4 doses post-procedure1211/6018.3n.s.Aspirin + batroxobin3/515.9Piaggesi et al [49]ObservationalPTA with or without stentingn.m.Aspirin or clopidogrelAspirin 100 mg/day, or clopidogrel 75 mg/day (if aspirin-intolerant). In case of stenting, patients received both indefinitely, alone, or + sulodexide 25 mg bid per os (upon discharge)63/2313.04n.s.Aspirin or clopidogrel + sulodexide3/2711.11Limb salvage and survival ratesWang et al [34]RCTIntraluminal and/or subintimal angioplastyFemoro-popliteal and infra-poplitealAspirinAspirin (100 mg/day) from admission day to at least 12 months if no side effects.…”
Section: Resultsmentioning
confidence: 99%
“…Batroxobin (5 IU/0.5 ml), 2 doses before and 4 doses post-procedure1241/267 (lesion)15.4n.s.Aspirin + batroxobin28/244 (lesion)11.4 Major amputation (above ankle amputation) Wang et al [34]RCTIntraluminal and/or subintimal angioplastyFemoro-popliteal and infra-poplitealAspirinAspirin (100 mg/day) from admission day to at least 12 months if no side effects. Batroxobin (5 IU/0.5 ml), 2 doses before and 4 doses post-procedure1211/6018.3n.s.Aspirin + batroxobin3/515.9Piaggesi et al [49]ObservationalPTA with or without stentingn.m.Aspirin or clopidogrelAspirin 100 mg/day, or clopidogrel 75 mg/day (if aspirin-intolerant). In case of stenting, patients received both indefinitely, alone, or + sulodexide 25 mg bid per os (upon discharge)63/2313.04n.s.Aspirin or clopidogrel + sulodexide3/2711.11Limb salvage and survival ratesWang et al [34]RCTIntraluminal and/or subintimal angioplastyFemoro-popliteal and infra-poplitealAspirinAspirin (100 mg/day) from admission day to at least 12 months if no side effects.…”
Section: Resultsmentioning
confidence: 99%
“…Piaggesi et al evaluated efficacy of sulodexide as a supplementary therapy in patients with critical limb ischemia secondary to diabetes that underwent percutaneous endovascular angioplasty. In the group of patients who took sulodexide improvements in microcirculation functions and reduction of pain were confirmed; however, there were no differences in ulcer healing and frequency of amputations as compared with the control group [34]. Jin et al observed protective activity of sulodexide with regard to peripheral nerve damage caused by microvascular dysfunction in rats with induced diabetes [35].…”
Section: Diabetic Foot Syndromementioning
confidence: 98%
“…oceniali skuteczność sulodeksydu jako terapii pomocniczej u chorych z krytycznym niedokrwieniem kończyn w przebiegu cukrzycy, poddanych przezskórnej angioplastyce wewnątrznaczyniowej. U chorych, u których stosowano sulodeksyd, stwierdzono poprawę funkcji mikrokrążenia i redukcję nasilenia bólu, natomiast nie stwierdzono różnic w gojeniu się owrzodzeń i częstości amputacji w porównaniu z grupą kontrolną [34]. Jin i wsp.…”
Section: Zespół Stopy Cukrzycowejunclassified
“…Nineteen out of the 64 studies assessed for eligibility were excluded because they contained no quantitative data that was extractable [106][107][108][109][110][111][112][113][114], did not report any of the chosen endpoints [28,[115][116][117][118][119], their data were not stratified by pathology or treatment [120,121], data were reported without variance [122], or control data were only historical [123].…”
Section: Excluded Studiesmentioning
confidence: 99%